2017
DOI: 10.1002/prep.201700046
|View full text |Cite
|
Sign up to set email alerts
|

Hypergolic Studies of Ethanol Based Gelled Bi-Propellant System for Propulsion Application

Abstract: The experiments conducted in this study examined the hypergolicity and ignition delay of the formulated ethanol gelled fuel and hydrogen peroxide oxidizer bipropellant system. The hypergolicity and ignition delay data for bipropellant system are very important for propulsion applications. It was observed that the ethanol based gelled fuel systems were hypergolic with hydrogen peroxide (90% pure) in a presence of a suitable catalyst. The observed ignition delay was within the range of 10~50 ms, which was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Propellant is formulated from alcohol family by varying carbon chain length from ethanol to heptanol, stabilized with cellulose based gelling agent. In past [18,19], weight percent of the gelling agent was reduced up to 6 wt.%, in present studies this weight percent was further reduced. The weight percent (wt.%) of gelling agent for gelation with respect to the formulated gel propellant are discussed in the previous publications [6][7][8][17][18][19], this is done to dominate the parent propellant properties and to reduce the effect of gelling agent as much as possible, for better performance.…”
Section: Introductionsupporting
confidence: 47%
See 2 more Smart Citations
“…Propellant is formulated from alcohol family by varying carbon chain length from ethanol to heptanol, stabilized with cellulose based gelling agent. In past [18,19], weight percent of the gelling agent was reduced up to 6 wt.%, in present studies this weight percent was further reduced. The weight percent (wt.%) of gelling agent for gelation with respect to the formulated gel propellant are discussed in the previous publications [6][7][8][17][18][19], this is done to dominate the parent propellant properties and to reduce the effect of gelling agent as much as possible, for better performance.…”
Section: Introductionsupporting
confidence: 47%
“…The metal salts used are Manganese (II) acetylacetonate (C 10 H 14 MnO 4 , Sigma Aldrich) and Copper (II) chloride (Cucl 2 , Sigma Aldrich) which will be represented as MCAT and CCAT, respectively. The experimental setup (Figure 1) and methodology to calculate the ignition delays are similar to those discussed in reference [17][18][19]. Measured volume of oxidizer is introduced using Eppendorf dropper onto the propellant, catalyst mixture, with the high speed camera the events are recorded and the time is calculated from, when the propellant and oxidizer comes in contact to, first visible spark or flame, this provides us with the ignition delays.…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Today, gelation technology attracts much interest [23][24][25][26][27][28][29][30][31] for its potential to increase enthalpy using metal particles as additives, deliver greater stability, and increase storability in respect of liquid propellants. The gel propellant has increasing viscosity at a decreased shear rate in a storage, which can contribute to the storability of hydrogen peroxide as well.…”
Section: Introductionmentioning
confidence: 99%
“…The gel propellant has increasing viscosity at a decreased shear rate in a storage, which can contribute to the storability of hydrogen peroxide as well. Several studies [23,24,26,[31][32][33][34] have reported the hydrogen peroxide gelation process, which has been mainly for better stability and storability of H 2 O 2 without any additives of metal powers, and possibility of use of the H 2 O 2 gel as a hypergolic propellant combination. However, little research has been reported in regards to gel propellant decomposition.…”
Section: Introductionmentioning
confidence: 99%